2010
DOI: 10.1037/a0018445
|View full text |Cite
|
Sign up to set email alerts
|

Mental health professionals' adaptive responses to racial microaggressions: An exploratory study.

Abstract: This study examines adaptive responses that mental health professionals of color use to cope with racial microaggressions in their professional lives. Twenty-four mental health professionals from diverse ethnic backgrounds in the United States and Canada participated in focus groups discussing their experiences with racial microagressions and how they cope with them. Results of the analysis indicated that 8 primary coping themes illustrated strategies used by the participants. These include: identifying key is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…While there is literature on the health and mental health effects of race related stress and racial microaggressions (Hernandez, Carranza, & Almeida, 2010), very little research has focused on how this stress affects mood states. Efforts to understand the link between the different types of race related stress on specific mood states have been limited and more research is needed (Carter, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While there is literature on the health and mental health effects of race related stress and racial microaggressions (Hernandez, Carranza, & Almeida, 2010), very little research has focused on how this stress affects mood states. Efforts to understand the link between the different types of race related stress on specific mood states have been limited and more research is needed (Carter, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The subjectivity and uncertainty surrounding microaggressions makes even those who face them regularly have difficulty in knowing how to respond (Hernández, Carranza, and Almeida 2010). Sue (2010) suggested that teachers should facilitate dialogs on microaggressions in the classroom but not directly control the content of those dialogs.…”
Section: Teachers' Responses To Microaggressionsmentioning
confidence: 99%
“…However, very few studies have explored the coping mechanism that has included culture as one of the variable of investigation (with the exception of Hernandez et al 4 ). These authors stressed the importance of mentoring health professionals of colour to help them navigate the professional terrain.…”
Section: Microaggressions Of Caregiver Employees: What Has Social Wormentioning
confidence: 99%
“…We suggest that even in democratic and multiculturalism countries like Canada, microaggressions are a form of aversive racism as they are often discreet, subtle and rationalized by the perpetrator. In recent years, evidence in scholarly literature has highlighted the detrimental impact of microaggressions on racial and ethnic minorities' psychological (mental or emotional) selves 3,4 and self-esteem 2 . Unlike overt racism, the complex, invisible, and subtle nature of microaggressions make them problematic for the perpetrator and victim 3 .…”
Section: Introductionmentioning
confidence: 99%